1999
DOI: 10.1002/j.2161-4296.1999.tb02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric Zenith Delay Prediction Accuracy for High-Precision GPS Positioning and Navigation

Abstract: In this paper, we determine mean bias and root-mean-square RMS scatter for a large number of zenith tropospheric propagation delay prediction models developed in the last few decades by comparing the models against ray-tracing results using a 1-year data set of radiosonde profiles. We conclude that the hydrostatic zenith delay can be predicted with submillimeter accuracy, provided that accurate measurements of station pressure are available. For wet zenith delay, the models differ significantly in accuracy, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 13 publications
0
23
0
6
Order By: Relevance
“…Considering all the eight stations together the mean of the absolute difference for SAAS and Unified model are 1.57 and 0.96 cm, respectively. In the case of wet delay, the Unified models developed in the present analysis are much better than the existing models (Ifadis, 1986;Mendes and Langley, 1998). The mean absolute difference of the unified model based on e S varies from about 4 to 5 cm, whereas in case of other two global models it varies from about 5 to 11 cm.…”
Section: Validation Of Unified Modelsmentioning
confidence: 79%
See 2 more Smart Citations
“…Considering all the eight stations together the mean of the absolute difference for SAAS and Unified model are 1.57 and 0.96 cm, respectively. In the case of wet delay, the Unified models developed in the present analysis are much better than the existing models (Ifadis, 1986;Mendes and Langley, 1998). The mean absolute difference of the unified model based on e S varies from about 4 to 5 cm, whereas in case of other two global models it varies from about 5 to 11 cm.…”
Section: Validation Of Unified Modelsmentioning
confidence: 79%
“…It would be worth in this context to compare the above relation with those reported by other investigators. Mendes and Langley (1998) …”
Section: Article In Pressmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these models and methods are only suitable for a kinematic station on the ground (Xu, 2000(Xu, , 2007. If the kinematic station is several kilometers higher than the ground reference stations, the precisions of tropospheric delays from these models will be decreased rapidly (Collins and Langley, 1997;Mendes and Langley, 1998). Therefore, it is necessary to creating a more suitable troposphere model for high altitude kinematic stations, such as airplane, airship and INSAR.…”
Section: Introductionmentioning
confidence: 97%
“…Some models are explicitly dependent on the surface meteorological data, while others are site dependent (the latitude and the height are required) and/or day-of-year dependent. Mendes and Langley (1998) assessed a number of zenith delay models using a one-year data set of radiosonde profiles from 50 stations distributed worldwide. They concluded that the Saastamoinen model (Saastamoinen 1973) is the most accurate with sub-millimeter bias and RMS scatter for the hydrostatic zenith delay with respect to the benchmark values.…”
Section: Introductionmentioning
confidence: 99%